Abnormal cortical excitability in sporadic but not homozygous D90A SOD1 ALS. Issue 9 (16th August 2005) - Turner, M R; Osei-Lah, A D; Hammers, A; Al-Chalabi, A; Shaw, C E; Andersen, P M; Brooks, D J; Leigh, P N; Mills, K R
Abstract : Background: Excitotoxicity is one pathogenic mechanism proposed in amyotrophic lateral sclerosis (ALS), and loss of cortical inhibitory influence may be contributory. Patients with ALS who are homozygous for the D90A superoxide dismutase-1 ( SOD1 ) gene mutation (homD90A) have a unique phenotype, associated with prolonged survival compared with patients with sporadic ALS (sALS). In this study, transcranial magnetic stimulation (TMS) was used to explore cortical excitation and inhibition. Flumazenil binds to the benzodiazepine subunit of the GABAA receptor, and 11 C-flumazenil positron emission tomography (PET) was used as a marker of cortical neuronal loss and/or dysfunction, which might in turn reflect changes in cortical inhibitory GABAergic mechanisms. Methods: Cortical responses to single and paired stimulus TMS were compared in 28 patients with sALS and 11 homD90A patients versus 24 controls. TMS measures included resting motor threshold, central motor conduction time, silent period, intracortical inhibition (ICI), and facilitation. 11 C-flumazenil PET of the brain was performed on 20 patients with sALS and nine with homD90A. Statistical parametric mapping was used to directly compare PET images from the two patient groups to identify those areas of relatively reduced cortical 11 C-flumazenil binding that might explain differences in cortical excitability seen using TMS. Results: Increased cortical excitability, demonstrated by reduction in ICI, was seen in the patients with sALS but not the homD90A patients. A relative reduction in cortical 11 C-flumazenil binding was found in the motor and motor association regions of the superior parietal cortices of the patients with sALS. Conclusions: A cortical inhibitory deficit in sALS was not demonstrable in a homogeneous genetic ALS population of similar disability, suggesting a distinct cortical vulnerability. 11 C-flumazenil PET demonstrated that neuronal loss/dysfunction in motor and motor association areas may underlie this difference. The corollary, that there may be relative preservation of neuronal function in these areas in the homD90A group, has implications for understanding the slower progression of disease in these patients.